Efek Pemberian Solid Dan Biourine Sapi Terhadap Pertumbuhan Kakao (Theobroma cacao L.) - Sahrudin Siregar; Yusmaidar Sepriani; Siti Hartati Yusida Saragih (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2021)
This research has been carried out in Labuhanbatu University’s North Sumatera Experimental Field. Starting in April 2020 until completion. The height of the placa ranges from ± 25 meters above sea level with a flat topography. This study aims to determine the effect of giving Solid and Biourine Cow on the growth of cocoa seedlings. This study used a factorial randomized block design (RBD) with 2 factors that were examined and repeated 3 times. The treatment are: Solid Fertilizer (S) treatment factor with 3 levels, namely: S0= No treatment (control), S1= 100 g Solid/polybag and S2= 200 g Solid/polybag. The second factor was giving Cow Biourine (B) with 3 levels, namely: B0= without treatment (control), B1= 150 ml/500 ml water polybag and B2= 300 ml/500 ml water/polybag. The number of treatment combinations 3x3= 9 treatment combinations namely: S0B0, S1B0, S2B0, S0B1,S1B1, S2B1, S0B2, S1B2 and S2B2. The data from the obsevations were analyzed using analysis of variance (ANOVA) and continued with the mean difference testKeywords: Solid, Beef Biourine, Cocoa, Growth